Cellular and molecular mechanisms involved in the protective effects of Aerva Lanata Linn.on airways remodeling in experimental model of bronchial asthma in rats - Sharma, Hemlata; Gulati, Kavita; Ray, Arunabha (Asian Journal of Pharmaceutical Research and Development, 2024)
Bronchial asthma is a chronic inflammatory respiratory disease characterized by bronchoconstriction and hyperresponsiveness of the bronchial airways. The treatment for bronchial asthma is mainly aimed at relieving symptoms by bronchodilators and controlling asthmatic attacks with anti-inflammatory agents. These therapeutic strategies are associated with several adverse drug effects and high cost that may negatively affect the compliance to therapy. Chronic asthma also results in structural remodeling of the airways which enhances the incidence of refractory asthma and increases morbidity/mortality. It is therefore important to explore adjuncts from alternative forms of therapy to compliment/supplement the conventional treatment. The study assessed the effects of Aerva Lanata Linn., a medicinal plant used in the traditional systems of medicine, on airway remodeling in an experimental model of asthma in rats. Wistar rats were immunized on day 0 with ovalbumin and Al(OH)3 and challenged with aerosolized ovalbumin from day 15 to 22. The rats were treated orally with various doses of standardized aqueous extract of whole plant of Aerva Lanata Linn. or prednisolone (10 mg/kg) for 22 days. After 24 hrs of last challenge, blood, bronchoalveolar lavage (BAL) fluid and lung tissue were collected and assayed for markers of structural remodeling viz, (a) cytokine levels (TGF-β and IL-13); (b) hydroxyproline content, and (c) histopathology. The results showed that Aerva Lanata Linn. markedly reduced the levels of TGF-β, IL-13 in both blood and BAL fluid and hydroxyproline content in lung homogenates. Histopathological examination of lung tissue confirmed the modulatory effects of Aerva Lanata Linn. on airway remodeling as evidenced by reductions in goblet cell hyperplasia, inflammatory cells infiltration and sub epithelial fibrosis, as compared to that in the experimental (disease control) group. The results showed that Aerva Lanata Linn. Attenuated the histopathological changes and biochemical markers of airway remodeling by altering the levels of IL-13 and TGFβ, and the study suggested that it could be beneficial in cases of chronic bronchial asthma.